A single-step synthesis of nitrogen-doped graphene sheets decorated with cobalt hydroxide nanoflakes for the determination of dopamine - Shahid, M.M.; Ismail, A.H.; Al-Mokaram, A.M.A.A.A.; Vikneswaran, R.; Ahmad, S.; Hamza, A.; Numan, A. (Taylor & Francis, 2017)
Nitrogen-doped reduced graphene oxide (NrGO) sheets decorated with Co(OH)2 nanoflakes were prepared by a single-step hydrothermal process. The morphological and structural characterizations of as synthesized NrGO@Co(OH)2 nanoflakes were performed by field emission scanning electron microscopy (FESEM), EDX-mapping and X-ray diffraction (XRD). NrGO@Co(OH)2 nanoflakes modified glassy carbon electrode (GCE) was used for electrochemical sensing of dopamine in neutral medium. The nanocomposite modified electrode showed enhanced electrochemical sensing ability for the detection of dopamine and the limit of detection (LoD) was found to be 0.201 μM with a sensitivity value of 0.0286 ± 0.002 mA mM−1. Interference studies revealed that NrGO@Co(OH)2─GCE endow excellent selectivity for DA detection even in the presence of higher concentration of common co-existing physiological interfering analytes. Additionally, proposed sensor demonstrated excellent performance in urine samples with promising reproducibility and stability.